Juvenile dermatomyositis - Our experience in the diagnosis and treatment of the disease - Gjurkova-Angelovska, Beti; Kacarska, Rozana; Kuzevska-Maneva, Konstandina; Jovanovska, Vesna; Neshkovska-Sumenkovska, Marija; Murtezani, A; Georgieva, Daniela (Medical Faculty, Ss. Cyril and Methodius University in Skopje, 2018)
Juvenile dermatomyositis (JDM) is a systematic, autoimmune and inflammatory muscles disease and vasculopathy which affects children younger than 18. Primarily it is the skin and skeletal muscles that are affected. JDM is a rare chronic condition in juveniles which decreases the quality of life in patients affected by it. Even though there has been improvement with the disease forecast and outcome with the therapy protocols during the last decade, JDM is a condition still associated with a significant morbidity and mortality rate. Primarily, the proximal groups of muscles and skin are affected. JDM diagnosis is based on 5 criteria, set by Bohan and Peter in 1975. Typical skin changes combined with other 3 criteria are vital to set the diagnosis. In 2006, additional 4 diagnostic criteria were introduced, which occurred due to the non invasive approach to the diagnosis. The purpose of the abstract is to present three patients with JDM, our experience setting the diagnosis, the different clinical course and therapy protocols applied in the treatment. The therapeutic approach in patients with JDM is multidisciplinary, implemented according to protocols, so a long-term follow-up is necessary. New therapeutic opportunities are a challenge, especially for patients with severe form of the disease, in order for them to have an improved quality of life, without any limitations in their everyday life and with lowered unwanted effects by the applied therapy. Therefore, an individualised therapeutic protocol for each patient is needed.
Јувенилен дерматомиозитис - наши искуства во дијагноза и третманот на болеста
Keywords: juvenile dermatomyositis; skin; skeletal muscles